2020
DOI: 10.1016/j.biopsycho.2019.107785
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral inhibition and EEG delta-beta correlation in early childhood: Comparing a between-subjects and within-subjects approach

Abstract: Heightened delta-beta correlation has been conceptualized as reflecting exaggerated neural regulation and has been implicated in anxiety. Behavioral inhibition (BI) is a temperament characterized by wariness to novelty and is a robust predictor of anxiety, but delta-beta correlation has not been investigated in relation to childhood BI. We examined the relation between BI and between-subjects (i.e., across participants) and within-subjects (i.e., across data epochs) measures of baseline EEG delta-beta correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 59 publications
3
31
3
Order By: Relevance
“…A very recent study (Poole and Schmidt, 2019) found that preschool children who have unsteady and temperamental antecedents of SAD exhibited relatively high frontal delta-beta correlation, as reported in and Poole et al (2020). It is obvious that although the overall coupling in frontal cross-frequency in children with SAD in this study is stronger, this pattern seems to be controlled primarily by the right frontal lobe when examining the separate hemispherical coupling.…”
Section: Delta-beta Coupling In the Anticipation Statesupporting
confidence: 49%
“…A very recent study (Poole and Schmidt, 2019) found that preschool children who have unsteady and temperamental antecedents of SAD exhibited relatively high frontal delta-beta correlation, as reported in and Poole et al (2020). It is obvious that although the overall coupling in frontal cross-frequency in children with SAD in this study is stronger, this pattern seems to be controlled primarily by the right frontal lobe when examining the separate hemispherical coupling.…”
Section: Delta-beta Coupling In the Anticipation Statesupporting
confidence: 49%
“…However, the functional significance of delta-beta correlation is not a foregone conclusion. Some researchers have posited that heightened delta-beta correlation is a maladaptive neural process associated with over-control and emotion dysregulation, which is supported by empirical work reporting heightened delta-beta correlation in relation to observed fear in toddlers (Najjar & Brooker, 2017;Phelps, Brooker, & Buss, 2016), behavioral inhibition in children (Poole, Anaya, & P erez-Edgar, 2020), anxiety-related profiles in adults (e.g., Knyazev, Schutter, & van Honk, 2006;Miskovic, Moscovitch, et al, 2011;Miskovic et al, 2010;van Peer, Roelofs, & Spinhoven, 2008), and in children of socially anxious parents (Miskovic, Campbell, et al, 2011).…”
Section: Frontal Delta-beta Correlation and Affective Stylementioning
confidence: 99%
“…The number of cleaned segments was entered as a covariate in our models to control for variation in proportion of available data. Power values across target electrodes (Poole et al, 2020) were averaged to create composites for the Frontal (F3, Fz, F4), Central (C3, Cz, C4), and Parietal (P3, Pz, P4) regions based on the 10-20 System of Electrode Placement.…”
Section: Eegmentioning
confidence: 99%
“…Similarly, temperamental antecedents of anxiety such as behavioral inhibition (BI) have been associated with stronger delta-beta coupling (Poole, Anaya, & P erez-Edgar, 2020). BI is a temperament profile characterized by shy, hypervigilant, and fearful behaviors in novel social situations that typically would not be interpreted as threatening (Garc ıa Coll, Kagan, & Reznick, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation